THEORETICAL ASPECTS AND SPECIFIC CHARACTERISTICS OF CORPORATE MANAGEMENT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The state examines the theoretical aspects of corporate governance in the world and in Uzbekistan and its features.